Les changements en foret tropicale: vers de nouvelles formes de gouvernance - Nasi, Robert; Gueneau, S. (2007)
Significant changes in forest management methods — e.g., granting of concessions in state-owned forests, introduction of forest planning, low-impact logging methods — have occurred in the three major tropical forest regions since the 1980s when forest issues became topics of worldwide concern. The main focuses of discussions between the North and the South, between the world of conservation and the world of development, have also shifted as new forms of governance where non-state players are more heavily involved in forestry affairs gained ground. These changes lead some players to oppose new instruments — in particular payment for ecosystem services — to other, currently implemented ones — in particular forest planning. We argue on the contrary that forest policies would derive cumulative benefit from using both tools.